PERSEPSI KEPALA DESA TERHADAP SUSTAINABLE DEVELOPMENT GOALS (SDGS) KE-8 DI DESA WISATA KAYU KEBEK KABUPATEN PASURUAN PROVINSI JAWA TIMUR - Ahmad Feryan Perwira Yudha; Havidz Ageng Prakoso; Agus Hari Wibawa (LPPM Universitas Abdurrab, 2025)
National development policy focuses on sustainability in all sectors, including tourism. The development of tourism villages that prioritize community empowerment and active participation is one manifestation of this policy direction. Continuous efforts are needed to find solutions to these issues. This study aims to analyze the views of the Village Head of Kayu Kebek on the 8th Sustainable Development Goal (SDG) and to examine the implementation of the tourism village program in supporting sustainable economic growth. A mixed methods approach was used, incorporating the Intermestik and Triple Bottom Line frameworks, as well as the Sustainable Development Goals (SDGs). Primary data was obtained through direct observation (fieldwork), interviews, and the distribution of questionnaires. Secondary data was obtained from annual reports from relevant institutions and from books, journals, articles, and regulations used to elaborate and answer the research questions raised. The results of the study show that the progressive views of the village head encourage community involvement in sustainable development. The implementation of SDG 8-based programs has had a positive impact on local economic growth, although there are challenges in terms of information dissemination and community training.